Atomic hydrogen in IllustrisTNG galaxies: the impact of environment parallelled with local 21-cm surveys. Issue 4 (20th December 2018) - Stevens, Adam R H; Diemer, Benedikt; Lagos, Claudia del P; Nelson, Dylan; Pillepich, Annalisa; Brown, Toby; Catinella, Barbara; Hernquist, Lars; Weinberger, Rainer; Vogelsberger, Mark; Marinacci, Federico
ABSTRACT: We investigate the influence of environment on the cold-gas properties of galaxies at$z$  = 0 within the TNG100 cosmological, magnetohydrodynamic simulation, part of the IllustrisTNG suite. We extend previous post-processing methods for breaking gas cells into their atomic and molecular phases, and build detailed mocks to comprehensively compare to the latest surveys of atomic hydrogen (H i ) in nearby galaxies, namely ALFALFA and xGASS. We use TNG100 to explore the H i content, star formation activity, and angular momentum of satellite galaxies, each as a function of environment, and find that satellites are typically a factor of ≳3 poorer in H i than centrals of the same stellar mass, with the exact offset depending sensitively on parent halo mass. Due to the large physical scales on which H i measurements are made (∼45–245 kpc), contributions from gas not bound to the galaxy of interest but in the same line of sight crucially lead to larger H i mass measurements in the mocks in many cases, ultimately aligning with observations. This effect is mass-dependent and naturally greater for satellites than centrals, as satellites are never isolated by definition. We also show that H i stripping in TNG100 satellites is closely accompanied by quenching, in tension with observational data that instead favour that H i is preferentially stripped before star formation is reduced.